2013
DOI: 10.1080/10810730.2012.727961
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Colonoscopy Barriers and Facilitators Among Urban African American Patients and Their Medical Residents

Abstract: African Americans suffer from higher colorectal cancer morbidity and mortality than do Whites, yet have the lowest screening rates. To understand barriers and facilitators to colorectal cancer screening, this study used perceptual mapping (multidimensional scaling) methods to compare patients' perceptions of colonoscopy and general preventive health practices to those of their doctors in a general internal medicine clinic in a large urban hospital. African American patients (n = 102) were surveyed about their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…Studies reported several types of patient fear: 1) fear of pain during colonoscopy; 2) fear of invasion during colonoscopy; 3) fear of bowel preparation; 4) fear of sedation or of hospital setting; and 5) fear of receiving a cancer diagnosis. 1822, 2425, 2728,3032 Fear of perceived “invasion” during colonoscopy was a common theme among African American males in particular. 1821,24,2728,30 Male respondents in focus groups and cognitive interviews described colonoscopy as “offensiveness,” “violating,” and “treading on my masculinity.” 18,24,27 Cancer-related fear stemmed from concerns about being diagnosed with cancer 19, 21, 25, 28,30 and of cancer treatment.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies reported several types of patient fear: 1) fear of pain during colonoscopy; 2) fear of invasion during colonoscopy; 3) fear of bowel preparation; 4) fear of sedation or of hospital setting; and 5) fear of receiving a cancer diagnosis. 1822, 2425, 2728,3032 Fear of perceived “invasion” during colonoscopy was a common theme among African American males in particular. 1821,24,2728,30 Male respondents in focus groups and cognitive interviews described colonoscopy as “offensiveness,” “violating,” and “treading on my masculinity.” 18,24,27 Cancer-related fear stemmed from concerns about being diagnosed with cancer 19, 21, 25, 28,30 and of cancer treatment.…”
Section: Resultsmentioning
confidence: 99%
“…The existing literature demonstrates that competing factors such as personal or financial obligations, 30 life stressors, 30 an inability to find transportation, 21, 25, 30, 34 and concern about other more pressing illness or comorbidity 35 also present barriers to colonoscopic screening.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…9 The Eight I's represent: (1) Intensity, (2) Importance, (3) Impact/interference, (4) Instances, (5) Imani-intercession, (6) Interventions, (7) Irritating effects, and (8) Inquiry of pain relief ( Figure 1 and Table 1). …”
mentioning
confidence: 99%